1982
DOI: 10.1042/bj2050361
|View full text |Cite
|
Sign up to set email alerts
|

Formation of complement subcomponent C1q-immunoglobulin G complex. Thermodynamic and chemical-modification studies

Abstract: The interaction between the complement subcomponent C1q and immunoglobulin G was investigated under a variety of experimental conditions. Formation of the subcomponent C1q--immunoglobulin G complex was shown to be an equilibrium process. Thermodynamic studies of the effect of varying the ionic strength indicate that over the salt range 0.15--0.225 M-NaCl the binding of subcomponent C1q to immunoglobulin aggregates releases 9--12 salt ions (Na+ and/or Cl-), illustrating the importance of ionic interactions for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…The modification was minimal to ensure that there was: (1) no alteration in either conformational integrity or the antigen binding capacity of the IgG molecules measured by CD spectra and precipitin curves; (2) specific labelling of few lysine residues. The specific activity of the modifying acetate groups indicated that there was 1.2 + 0. agree with our results for acetic anhydride modified IgC where 2.2 + 0.3 modified lysine residues on IgG changed the binding affinity 29-fold [21]. This is a significant change in binding affinity since modifications of arginine and tryptophan residues have no effect on Clq binding affinity for IgG.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The modification was minimal to ensure that there was: (1) no alteration in either conformational integrity or the antigen binding capacity of the IgG molecules measured by CD spectra and precipitin curves; (2) specific labelling of few lysine residues. The specific activity of the modifying acetate groups indicated that there was 1.2 + 0. agree with our results for acetic anhydride modified IgC where 2.2 + 0.3 modified lysine residues on IgG changed the binding affinity 29-fold [21]. This is a significant change in binding affinity since modifications of arginine and tryptophan residues have no effect on Clq binding affinity for IgG.…”
Section: Resultssupporting
confidence: 91%
“…Immune rabbit IgG (anti-ovalbumin) was prepared asin [21] thenmodified with [ 1-14C]aceticanhydride which reacts with lysine residues [ 19,201. The conditions of modification, acetate buffer at pH 5 .O and O"C, are extremely mild and do not lead to protein denaturation.…”
Section: Modification Of Iggmentioning
confidence: 99%
See 2 more Smart Citations
“…The binding of lZSl-labelled Clq to immune complexes was measured using the methods of [7]. The fluorescence of protein-bound ANS was measured at 490 _+ 5 nm, following excitation at 390 _+ 5 nm, using an Aminco SPF-500 spectrofluorimeter, with the cell-holders thermostatted at 37°C.…”
Section: Methodsmentioning
confidence: 99%